Fiscal policy uncertainty and its effects on the real economy: German evidence - Joscha Beckmann; Robert Czudaj (Chemnitz University of Technology, Faculty of Economics and Business Administration, 2020)
This paper introduces a new measure of fiscal policy uncertainty based on the disagreement among professional forecasters. We analyze different patterns of this measure for the German economy for a sample period from November 1995 to April 2018 and also use Italian data for comparison. Especially, we examine the impact of the introduction of the German 'debt brake' on fiscal policy uncertainty. Finally, we conduct an impulse response analysis to investigate the effect of fiscal policy uncertainty on the real economy and we provide robust evidence that fiscal policy uncertainty significantly decreases the growth rate of industrial production. The corresponding effect is robust to various sensitivity checks and exceeds the impact of a general measure of economic policy uncertainty. In general, the negative effect on the real economy might be explained by lower hiring and investment by firms, higher costs of financing due to risk premia and lower consumption spending as a result of precautionary savings.
Keywords: E62; 330; Disagreement; Expectations; Fiscal policy; Survey data; Uncertainty; VAR